Comparison of Wireless Sensor Network Routing Protocols under Gamma Radiation for Nuclear and Space Applications. (1st August 2016) - Nishimura, Michael; Liu, Yu; Li, Liqian; Colins, Karen
Abstract: With the advancement of computer and communication technologies, wireless sensor networks (WSNs) are increasingly used in nuclear and space applications, both of which may require operation in a high-intensity radiation environment. Gamma rays' damaging mechanisms in semiconductor devices are described as, and specifically linked to, semiconductor property changes in detectors, transistors, and integrated circuits. Radiation damage is cumulative and can result in the premature failure of WSN nodes. Failed WSN nodes decrease the quality of service of the entire WSN and then delay immediate response to severe accidents. This paper focuses on evaluating the performance of WSN routing protocols in a gamma-ray radiation environment. The probability density function of a Weibull distribution was used to model failures of individual nodes in simulated WSNs. The distribution parameters are based on results of radiation damage tests performed on semiconductor devices in the Gamma-220 facility ( 60 Co source) at the Canadian Nuclear Laboratories. Simulation of the routing protocols [LEACH (Low Energy Adaptive Clustering Hierarchy), LEACH-C (LEACH-Centralized), Stat-Clus (Static Clustering), MTE (Minimum Transmission Energy), and PEGASIS (Power-Efficient Gathering in Sensor Information Systems)] through NS2 (Network Simulator 2) and the resulting performance analyses could provide useful design insights and considerations for nuclear and space applications. The performance of WSN routing protocols is evaluated for the first time in a gamma-ray radiation environment for nuclear and space applications.